Christian Minority Religious Education in Muslim-Majority Cumedak: Ideals, Realities, and Paleran Hall Study - El Adibah, Elisa Dourotun Nafis; Fiddini, Muktazzah; Wicaksono, Syafril; Habiba, Iefone Shiflana; Al Asy Ari, M Khoirul Hadi (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3626, 2024)
Religious education is an important aspect that acts as the formation of the morals and character of each individual. This is supported by various religions in Indonesia. There are several obstacles to uneven religious education , especially for minorities. So with this , the researcher aims to analyze the application of religious education for Christian students in a Muslim- majority village with a focus on Paleran Hamlet , Cumedak Village , Jember Regency. The application of religious education in Paleran Hamlet is analyzed between ideality and illusion . The researcher wants to study related: One, how is the implementation of religious education for Christian minorities in Paleran Hamlet , Cumedak Village , Sumberjambe District , Jember Regency? Two, What is the effect of the application of religious education for Christian minorities in Paleran Hamlet , Cumedak Village , Sumberjambe District , Jember Regency in the dynamics of ideality and reality ? This research uses empirical research methods with a literature study approach based on a descriptive qualitative data approach . The results showed that the application of religious education for Christian students in Paleran Hamlet tends to be influenced by the dynamics of ideality and illusion . The dynamic of ideality contains the hope of Christian students to obtain proper religious education under the life of the majority of Islam in Cumedak Village . While the illusory dynamic means obstacles for students to get religious education due to factors such as lack of educator resources and inadequate quantity of minorities .The state implication of this study is that the government must strengthen equitable religious education policies to ensure minority students receive fair access, adequate educators, and protected religious rights regardless of demographic composition.